Deciphering the Potential of Rhizobium pusense MB-17a, a Plant Growth-Promoting Root Endophyte, and Functional Annotation of the Genes Involved in the Metabolic Pathway - Chaudhary, Twinkle; Gera, Rajesh; Shukla, Pratyoosh (Frontiers in Bioengineering and Biotechnology, 2021)
Plant growth-promoting rhizobacteria (PGPR) are the root endophytic bacteria used for the growth promotion and they have broader applications in enhancing the specific crop yield as a whole. In the present study, we have explored the potential of Rhizobium pusense MB-17a as an endophytic bacterium that was isolated from the roots of the mung bean (Vigna radiata) plant. Furthermore, it was sequenced and assembled to reveal the genomic potential associated with the plant growth-promoting traits. Interestingly, the root endophyte Rhizobium pusunse MB-17a showed all the essential PGPR traits which were determined by biochemical and PGPR tests. It was noted that this root endophytic bacteria significantly produced siderophore, indole acetic acid (IAA), ammonia, ACC deaminase and efficiently solubilized the phosphate. The maximum IAA and ammonia production was observed at 110.5µg/ml and 81µg/ml respectively. Moreover, the PGPR potential of this endophytic bacterium was also confirmed by a pot experiment for mung bean (Vigna radiata) which resulted, a substantial increase in the plant’s fresh weight by 76.1% and dry weight by 76.5% on the 60th day after inoculation of Rhizobium pusunse MB-17a. Also, there is a significant enhancement in the nodule number by 66.1% and nodule fresh weight by 162% at 45thday after inoculation with 100% field capacity after the inoculation of Rhizobium pusunse MB-17a. Besides this, the functional genomic annotation of Rhizobium pusunse MB-17a determined the presence of different proteins and transporters that are responsible for its stress tolerance and its plant growth-promoting properties. It was concluded that the unique presence of genes like rpoH, otsAB, clpB enhances the symbiosis process during adverse conditions in this endophyte. By the RAST (Rapid Annotation using Subsystem Technology) analysis the key genes involved in the production of siderophore, volatile compounds, indole, nitrogenase and amino acid were also predicted. In conclusion, the strain described in this study gives a novel idea of using such type of endophytes for improving the plant growth-promoting traits under different stress conditions for sustainable agriculture.